Impact of Pandemic Financial Crisis to the Going Concern Audit Opinion Factors - Hidayat, Ahmad Hafid (Advances in Social Sciences Research Journal, 2022)
This study aims to further analyze the relationship between the characteristics, client relationship characteristics and environmental factors of auditors in issuing going concern audit opinions during pandemic financial crisis. By analyzing the effect of audit client tenure, litigation risk, and audit firm size on going-concern audit opinion and financial crisis due to COVID-19 as moderation. This study uses secondary data, financial statements and independent auditor reports of mining companies listed on the Indonesia Stock Exchange in period 2017-2020. The analytical method used is logistic regression. The results showed that the audit client tenure of public accountants and audit firm size had a significant negative effect on the issuance of going-concern audit opinions, while litigation risk had a significant positive effect on the issuance of going-concern audit opinions. Then the financial crisis due to Covid-19 had a significant positive effect on going-concern audit opinion but did not moderate the effect of audit client tenure, litigation risk, and audit firm size on going-concern audit opinion.